Convergence in patient–therapist therapeutic alliance ratings and its relation to outcome in chronic depression treatment. (4th July 2017) - Laws, Holly B.; Constantino, Michael J.; Sayer, Aline G.; Klein, Daniel N.; Kocsis, James H.; Manber, Rachel; Markowitz, John C.; Rothbaum, Barbara O.; Steidtmann, Dana; Thase, Michael E.; Arnow, Bruce A.
Abstract: Objective : This study tested whether discrepancy between patients' and therapists' ratings of the therapeutic alliance, as well as convergence in their alliance ratings over time, predicted outcome in chronic depression treatment.Method : Data derived from a controlled trial of partial or non-responders to open-label pharmacotherapy subsequently randomized to 12 weeks of algorithm-driven pharmacotherapy alone or pharmacotherapy plus psychotherapy. The current study focused on the psychotherapy conditions ( N  = 357). Dyadic multilevel modeling was used to assess alliance discrepancy and alliance convergence over time as predictors of two depression measures: one pharmacotherapist-rated (Quick Inventory of Depressive Symptoms-Clinician; QIDS-C), the other blind interviewer-rated (Hamilton Rating Scale for Depression; HAMD).Results : Patients' and therapists' alliance ratings became more similar, or convergent, over the course of psychotherapy. Higher alliance convergence was associated with greater reductions in QIDS-C depression across psychotherapy. Alliance convergence was not significantly associated with declines in HAMD depression; however, greater alliance convergence was related to lower HAMD scores at 3-month follow-up.Conclusions : The results partially support the hypothesis that increasing patient–therapist consensus on alliance quality during psychotherapy may improve treatment and longer term outcomes.